HUBUNGAN KADAR GLUKOSA DARAH DAN KADAR HbA1c DENGAN STATUS FUNGSI KOGNITIF PASIEN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT MARINIR CILANDAK TAHUN 2019 - Fadhilah Apriliandri; Mila Citrawati; Etra Ariadno (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Relationship between Blood Glucose Levels and Hba1c Levels with Cognitive Function Status of Type 2 Diabetes Mellitus Patients at the Cilandak Marine Hospital in 2019Background: Hyperglycemic and insulin resistance can lead to chronic complications in type 2 diabetes patients with long treatment such as macro vascular, micro vascular and neuropathic complication. This may cause alteration and disruption in various system, included the center of nerve system, that related to cognitive function. Objective: This research aimed to analyze the correlation between cognitive status with blood glucose levels and HbA1c level in type 2 diabetes mellitus patients at Marinir Cilandak Hospital. Methods: This research was an analytic observational research with the approach of Cross Sectional method. The study sample included populations with the inclusion and exclusion criteria of 40 respondents. Samples in this study was calculated using Consecutive Sampling. Results: The results showed multivariate analysis that the entire of the independent variables with cognitive status obtained p value = <0,001 (p <0,05). Conclusion: There was significant correlation between blood glucose levels and HbA1c levels with cognitive status in type 2 diabetes mellitus patients.